Step 1: Determine the conjugate of the denominator. ( to find the conjugate just change the sign of the imaginary part ).
In this example, the conjugate of $ \color{orangered}{ \frac{ 1 }{ 20 }+\frac{ 3 }{ 20 }i }\, $ is $ \color{blue}{ \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i } $.
Step 2: Multiply both the numerator and denominator by the conjugate:
$$\begin{aligned} \frac{ 1 }{ \frac{ 1 }{ 20 }+\frac{ 3 }{ 20 }i } &= \frac{ 1 }{ \frac{ 1 }{ 20 }+\frac{ 3 }{ 20 }i } \cdot \frac{ \color{blue}{ \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i } }{ \color{blue}{ \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i } } = \\[1 em] &= \frac{ 1 \cdot \left( \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i \right) }{ \left( \frac{ 1 }{ 20 }+\frac{ 3 }{ 20 }i \right) \cdot \left( \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i \right) } \end{aligned} $$Step 3: Simplify numerator and denominator (use $\color{blue}{i^2 = -1}$)
$$ \begin{aligned} 1 \cdot \left( \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i \right) &= 1 \cdot \frac{ 1 }{ 20 } + 1 \cdot \left(-\frac{ 3 }{ 20 } \,i \right) = \\[1 em] &= \frac{ 1 }{ 20 } -\frac{ 3 }{ 20 } \, i = \\[1 em] &= \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i\end{aligned} $$ $$ \begin{aligned} \left( \frac{ 1 }{ 20 }+\frac{ 3 }{ 20 }i \right) \cdot \left( \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i \right) &= \frac{ 1 }{ 20 } \cdot \frac{ 1 }{ 20 } + \frac{ 1 }{ 20 } \cdot \left(-\frac{ 3 }{ 20 } \,i \right) + \left( \frac{ 3 }{ 20 } \,i \right) \cdot \left(\frac{ 1 }{ 20 } \right) + \left( \frac{ 3 }{ 20 } \,i \right) \cdot \left(-\frac{ 3 }{ 20 } \,i \right) = \\[1 em] &= \frac{ 1 }{ 400 } -\frac{ 3 }{ 400 } \, i + \frac{ 3 }{ 400 } \, i -\frac{ 9 }{ 400 } \color{blue}{(-1)} = \\[1 em] &= \frac{ 1 }{ 40 }\end{aligned} $$Step 4: Separate real and imaginary parts:
$$ \frac{ 1 }{ \frac{ 1 }{ 20 }+\frac{ 3 }{ 20 }i } = \frac{ \frac{ 1 }{ 20 }-\frac{ 3 }{ 20 }i }{ \frac{ 1 }{ 40 } } = \frac{ \frac{ 1 }{ 20 } }{ \frac{ 1 }{ 40 } } + \frac{ -\frac{ 3 }{ 20 } }{ \frac{ 1 }{ 40 } } i= 2-6i $$